Prevalensi Telur Ascaris lumbricoides dan Trichuris trichiura pada Kotoran Kuku Tangan Murid Kelas I, II, dan III SD Negeri 013 Meranti Pandak Kecamatan Rumbai Pesisir Pekanbaru Serta Gambaran Faktor Risiko - Dwi Julianika Putri; Suri Dwi Lesmana; Tuti Restuastuti (Jurnal Ilmu Kedokteran, 2010)
Ascaris lumbricoides ( A.lumbricoides ) and Trichuris trichiura ( T.trichiura ) are Soil Transmitted Helminth. Infectiondue to these worms still become a public health problem in Indonesia especially in students at elementary schools.The purpose of this research is to know the prevalence of students with positive A.lumbricoides and T.trichiura egg intheir nail’s dirt and the risk factors that affected it. Data was collected by questionaire and by examining the nail’s dirtusing Ismid’s Modification Method to all of class I,II,III students with inclusion criteria (177 students ). The prevalenceof students with positive A. lumbricoides dan T. trichiura eggs in nail dirt was 44.06% and 2.82%. The prevalence ofA.lumbricoides and T.trichiura are higher at boys (58.16%), which are influenced by the parent’s education and socioeconomical condition. The most cases was found in students with bad habit of family’s toilet, hand washing aftertoilet, often play in ground, and the habit of nail-cutting.